Educação e liberdade: a circulação do pensamento pedagógico no Mercosul durante os anos de abertura política. - da Silva, André Gustavo Ferreira (Diálogos Latinoamericanos, 2015)
In this article we explore the notion of freedom expressed in the pedagogical thinking of the MERCOSUR countries (Argentina, Paraguay, Uruguay and Brazil) during the redemocratization period. We do a comparative study with emphasis on the ideas of autonomy and democracy in the current era. It is methodologically supported by bibliographic research using periodicals of large circulation in the pedagogical environment. It is concluded that the integration of pedagogical ideas in the region was driven by the connection of the teacher union movement, the progressive Catholic Church and even the conjunction of interests of sectors linked to private schools. The idea of liberty was represented through the defense of private freedom advocated by school owners, and also defended through the rereading of the New School by the middle sector of society. It was also understood as revolution of capitalist structures by the teacher union movement - which proposed the pedagogical process as counter-hegemonic - and as liberation by educators linked to Freire.